Kinetic Studies of Curing Reaction of Epoxy Resins - Desai, D.J. (Asian Journal of Chemistry, 2016)
The kinetic study of epoxy resins, using triethanolamine (TEA) as catalyst having different concentrations, were carried out for the various systems, viz., diglycidyl ether of bisphenol-A (DGEBA), epoxidized 2,4-dichlorophenol-1,2-dichlororoethane oligomer (EBPE) and phthalic anhydride (PA) as curing agent [1:1:2] the extent of reaction (P) was studied for above said systems at elevated temperature. Certain reactions for cure of epoxy resins were carried out with and without amine accelerator.